2020
DOI: 10.1155/2020/6303062
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Preterm Birth and Its Associated Factors: A Cross-Sectional Study at Butajira Hospital, Southern Nations, Nationalities, and People’s Region, Ethiopia

Abstract: Background. Preterm birth infants are at a greater risk of mortality and a variety of health and developmental problems; reliable data support that this rate is increasing in almost all countries. The purpose is to find the magnitude of preterm birth and its associated factors among newborns delivered at Butajira Hospital, Southern Nations, Nationalities, and People’s Region, Ethiopia. Methods. This hospital-based cross-sectional study was carried out on 304 maternity cards using the systematic sampling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Four studies were excluded due to lack of an outcome of interest or no reported outcome of interest [ 48 ], and the remaining one article was excluded due to a lack of access to the full text [ 49 ]. 23 studies [ 29 , 30 , 31 , 34 , 35 , 37 , 38 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were included in the final quantitative meta-analysis to estimate pooled preterm birth ( Figure 1 ).
Figure 1 PRISMA flow diagram of preterm birth in Ethiopia.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies were excluded due to lack of an outcome of interest or no reported outcome of interest [ 48 ], and the remaining one article was excluded due to a lack of access to the full text [ 49 ]. 23 studies [ 29 , 30 , 31 , 34 , 35 , 37 , 38 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were included in the final quantitative meta-analysis to estimate pooled preterm birth ( Figure 1 ).
Figure 1 PRISMA flow diagram of preterm birth in Ethiopia.
…”
Section: Resultsmentioning
confidence: 99%
“…Of those, three studies showed a significant association between the presence of at least one ANC visit with preterm birth [ 33 , 38 , 56 , 64 ] versus zero visits, and four studies showed absence of association between the presence of at least one ANC visit and preterm birth [ 29 , 37 , 50 , 55 ]. Seven primary studies showed there was a significant association between the frequency of four or more ANC visits versus less than or equal to four visits and preterm birth [ 30 , 33 , 51 ] and no association based on four studies [ 54 , 64 , 65 ]. Thus, the meta-analysis revealed that the presence of at least 1 ANC visit as well as having four or more frequent antenatal care visit interventions are modifiable predictors that reduce the odds of preterm birth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations